2017
DOI: 10.18632/oncotarget.21225
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat and metformin sensitize EGFR-TKI resistant NSCLC cells via BIM-dependent apoptosis induction

Abstract: There is a close relationship between low expression of BIM and resistance to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI). Vorinostat is a pan-histone deacetylase inhibitor (HDACi) that augments BIM expression in various types of tumor cells, however, this effect is attenuated by the high expression of anti-apoptotic proteins in EGFR-TKI resistant non-small cell lung cancer (NSCLC) cells. Vorinostat in combination with metformin – a compound that can inhibit anti-apoptotic proteins ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Numerous investigations have provided evidence implying a potential role for metformin in cancer treatment, and some also showed that metformin influences autophagy in many kinds of tumour cell lines, and it affects different types of cancer cells in different ways. As the previous study showed, metformin inhibited autophagy induced by gefitinib and vorinostat whose mechanism had not been clear; in this research, the same phenomenon was observed in osimertinib‐treated NSCLC cells, and metformin combined with osimertinib had a synergistic anti‐tumour effect. Studies have found that the effective mechanism of metformin in cancer cells may be due to cell cycle arrest induction, mTOR inhibition, JAK2/STAT signalling inhibition, immunomodulation, cytotoxic properties and autophagy regulation .…”
Section: Discussionsupporting
confidence: 59%
“…Numerous investigations have provided evidence implying a potential role for metformin in cancer treatment, and some also showed that metformin influences autophagy in many kinds of tumour cell lines, and it affects different types of cancer cells in different ways. As the previous study showed, metformin inhibited autophagy induced by gefitinib and vorinostat whose mechanism had not been clear; in this research, the same phenomenon was observed in osimertinib‐treated NSCLC cells, and metformin combined with osimertinib had a synergistic anti‐tumour effect. Studies have found that the effective mechanism of metformin in cancer cells may be due to cell cycle arrest induction, mTOR inhibition, JAK2/STAT signalling inhibition, immunomodulation, cytotoxic properties and autophagy regulation .…”
Section: Discussionsupporting
confidence: 59%
“…In a panel of non-small cell lung cancer (NSCLC) cell lines, MTF combined with an anti-IGF1R antibody inhibited IGF1R signaling and the combination of both MTF and anti-IGF1R antibody exerted additive inhibitory effects on cell viability [ 109 ]. In NSCLC cell lines that were resistant to EGFR tyrosine kinase inhibitors (TKIs), treatment with the pan-histone deacetylase inhibitor vorinostat and MTF synergistically improved sensitivity to the EGFR-TKI gefitinib [ 110 ]. Sensitivity was mediated by pro-apoptotic protein BCL2 like 11 (BCL2L11; alias, BIM) that induced apoptosis, whereas autophagy was significantly reduced by MTF.…”
Section: Pleiotropic Mtf Effects On Cancer: Basic and Preclinical mentioning
confidence: 99%
“…Adding metformin to gefitinib reduced proliferation and the anchorage‐independent colony‐forming ability of a panel of NSCLC cell lines . Chen et al found that metformin clearly inhibited antiapoptotic protein expression, increased BIM and BAX, leading to significantly improved sensitivity of gefitinib. It has been reported that metformin can revert resistance to gefitinib .…”
Section: Combination Of Metformin With Small Molecular Inhibitorsmentioning
confidence: 99%
“…Chen et al found that metformin clearly inhibited antiapoptotic protein expression, increased BIM and BAX, leading to significantly improved sensitivity of gefitinib. It has been reported that metformin can revert resistance to gefitinib . In xenografts with gefitinib‐resistant cancer cells, metformin blocked tumor growth and suppressed tumor relapse effectively.…”
Section: Combination Of Metformin With Small Molecular Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation